Routine Maintenance - (:unkn) unknown (My University, 2017)
Routines are a large part of our daily lives. They are the skills that we utilize to get through our day effortlessly. From tying our shoes to operating a vehicle, routines are repeated skilled behaviors often initiated and produced with little attention or conscious focus. While routines are an important part of our lives, they are neglected by much of the literature on intentional action. This has led to some criticism that the intention literature is over-intellectualized, and only focuses on behavior that has a concurrent conscious component. Further, some authors have even suggested that skilled behaviors like routines are not intentional whatsoever. This leads to the unfortunate conclusion that much of our daily behavior is not controlled by the agent, but by unconscious mechanisms. In this paper I hope to combat this view. I argue that we can understand routine behavior through a diachronic lens, where practice can be viewed as a conscious setting of a behavioral goal.
Keywords: Action; Free Will